Mechanically improved laser mode-locker comprising tapered fibers coated with graphene-polymer composite - Kang, Myungjin; Ryu, Bowon; Kovalchuk, Oleksiy; Cho, Inhun; Moon, Hyowon; Song, Yong-Won (2025 30TH OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE, OECC AND 2025 INTERNATIONAL CONFERENCE ON PHOTONICS IN SWITCHING AND COMPUTING, PSC, 2025)
We demonstrate a tapered-fiber mode-locker with enhanced durability given by graphenedispersed polymer coating. Tensile strength improvement of 80 % is achieved while preserving nonlinearity of graphene. Resultant device ensures stable and ultrashort pulse generation.